COMBATE EXPERIMENTAL AO ÃCARO ð˜—ð˜ð˜ ð˜“ð˜“ð˜–ð˜Šð˜–ð˜—ð˜›ð˜™ð˜œð˜›ð˜ˆ ð˜–ð˜“ð˜Œð˜ð˜ð˜–ð˜™ð˜ˆ (ASHM., 1879) COM INSETICIDAS EM PULVERIZAÃ‡ÃƒO E UM GRANULADO SISTÃŠMICO INCORPORADO AO SOLO - Mariconi, Francisco A. M.; Tardivo, JoÃ£o C.; Santos, Bento M.; DionÃsio, Antonio; Brunelli Jr., HÃ©rcules C.; Amorim Neto, Luiz A.; Fagan, Rubens (REVISTA DE AGRICULTURA, 2020)
COMBATE EXPERIMENTAL AO ÃCARO ð˜—ð˜ð˜ ð˜“ð˜“ð˜–ð˜Šð˜–ð˜—ð˜›ð˜™ð˜œð˜›ð˜ˆ ð˜–ð˜“ð˜Œð˜ð˜ð˜–ð˜™ð˜ˆ (ASHM., 1879) COM INSETICIDAS EM PULVERIZAÃ‡ÃƒO E UM GRANULADO SISTÃŠMICO INCORPORADO AO SOLO